PERLINDUNGAN HUKUM BAGI NASABAH DALAM PINJAMAN ONLINE DITINJAU DARI PERATURAN OTORITAS JASA KEUANGAN NOMOR 77/POJK.01/2016 TENTANG LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI - Cahyaning Putri, Etis; Atma Yolanda, Frida (Nusantara Hasana Journal, 2022)
The rapid development of technology has also brought changes to people’s lifestyles which are now increasingly diverse, this can be done quickly and easily with online-based services or using the internet, both in terms of shopping, ordering transportation, or conducting financial transactions, which currently has a very large presence. Popular in the community because it is supported by the emergence of many start-ups or start-ups that offer a variety of digital services such as payments, investments, loans, and financing. The research method used is an empirical or sociological research method whose data is obtained directly from the source and is obtained through interviews and real behavior through direct observation. The research was conducted by conducting and obtaining data and information related to online loans at the Banyuwangi Police and also interviews with 12 people in Banyuwangi Regency who had and/or used online loans. The results of the study show (1) The presence of the Fintech industry in offering digital-based financial products seems to open new doors for people who want to apply for loans. Then the government through the Financial Services Authority issued a Financial Services Authority Regulation hereinafter referred to as POJK Number 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services which regulates and supervises the development of P2PL. POJK Number 77/POJK.01/2016 as a legal basis that can be used to show evidence of the legitimacy of credit activities through online media. (2) The supervision carried out by the OJK is only for legal online loan companies, namely those that have been registered and received permission from the OJK, but for supervision of illegal online loan companies, the Investment Alert Task Force will be handled.